Technical guidelines for risk assessment of heavy metals in traditional Chinese medicines - Tian-Tian Zuo; Lei Zhang; Ying Wang; Li-Xing Nie; Ming-Rui Shen; Li-Na Liu; Jian-Dong Yu; Hong-Yu Jin; Feng Wei; Shuang-Cheng Ma (BMC, 2023)
Abstract Background Heavy metals are considered a global concern because they can deteriorate human health. This guideline aims to scientifically evaluate health risk of heavy metals in TCM and to propose a reference for decision making in developing TCM-related health policies. Methods Using a multidisciplinary approach, a steering committee oversaw the development of the guideline. To obtain a reasonable and accurate risk assessment, key exposure assessment parameters for TCM, e.g., exposure frequency (EF), exposure duration (ED), and daily ingestion rate (IR) were obtained from surveys. In addition, transfer rates for heavy metals from Chinese medicinal materials (CMM) to decoctions or preparations were examined. Results Based on the scientific theory of risk control, the guideline was designed systematically, and principles and procedures for the risk assessment of heavy metals in TCM were identified. The guideline can be utilized to assess the risk of heavy metals in CMM and Chinese patent medicines (CPM). Conclusion This guideline may help standardize the risk assessment of heavy metals in TCM, advance regulatory standards for heavy metals in TCM, and ultimately improve human health through scientific TCM usage in clinic.